Elementos para a compreensão do desenho anatômico: uma metodologia do ensino do desenho dinâmico da figura humana para estudantes de artes visuais - Jubran, Alexandre (2013)
The present work discusses the learning process of free hand drawing and particularly of the human figure drawing and languages and methodologies of that form of expression, and design models aimed at visual arts students. The reading texts related to the design and its meaning, the cognitive aspect and philosophies applied to the study of the figure gives the basis for reading lines of human object, offering a contemporary look to this as a learning experience, coupled with possible references to understanding of general forms of learning design, as well as its pedagogy. Besides the introduction and endnotes, the dissertation has five parts, dealing with topics such as drawing lines and their historical and contemporary models coexisting, learning through the assimilation of these, and the possible place of technique and proportions of the design considerations with design pedagogy, the teacher as mediator and systematization of the development process of the author as a teacher of classes drawing freehand.